Enhancing religious tolerance among students through an integrative approach in elementary school teachers: a mixed-methods study - Moh Masduki; Makherus Sholeh; Mowafg Abrahem Masuwd; Tri Wahyudi Ramdhan (Journal of Integrated Elementary Education, 2026)
Promoting religious tolerance is essential in multicultural societies, particularly in Indonesia, where diverse religious identities coexist. This study aimed to examine the impact of a religious identity-based seminar on prospective elementary school teachers’ self-efficacy, beliefs about religious diversity, and stereotype awareness. Using a mixed methods design, 70 teacher candidates were divided into an intervention group and a control group. The intervention group participated in an eight-week seminar focused on religious identity, stereotype reflection, and inclusive pedagogy, while the control group attended conventional diversity training. Quantitative data were collected using validated scales for self-efficacy, curriculum beliefs, and stereotype awareness, and were analyzed using repeated-measures ANCOVA. Results showed that the intervention group experienced significant improvements across all three domains, with large effect sizes noted particularly in stereotype awareness (η² = 0.19). Qualitative data from reflective responses supported these findings, revealing increased self-awareness, implementation of inclusive teaching strategies, and recognition of challenges such as a lack of resources and fear of miscommunication. The seminar effectively encouraged critical reflection and practical application, equipping participants to foster interfaith understanding in their future classrooms. This study underscores the value of culturally responsive, identity-focused training in teacher education and highlights the need for policy and institutional support to sustain inclusive teaching practices in diverse educational contexts.